2006
DOI: 10.1063/1.2177035
|View full text |Cite
|
Sign up to set email alerts
|

Assessing The Effectiveness Of A Computer Simulation In Conjunction With Tutorials In Introductory Physics In Undergraduate Physics Recitations

Abstract: Abstract. We present two studies documenting the effectiveness of the use of a computer simulation with Tutorials in Introductory Physics 1 in a transformed college physics course. 2 An interactive computer simulation, entitled the Circuit Construction Kit (CCK), 3, 4 was introduced to investigate its possible impact on students' conceptual understanding. The first study compared students using either CCK or real laboratory equipment to complete two Tutorials on DC circuits. The second study investigated the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 6 publications
1
7
0
10
Order By: Relevance
“…Several studies have found that computer simulations can be just as useful, if not more beneficial, than paper-and-pencil activities or standard equipment. [1][2][3][4] Keller et al (2005) found in one study that there was a slight increase in student conceptual performance soon after using a computer simulation with Tutorials in Introductory Physics [5] compared to students with real equipment, but that this effect vanished upon re-examination several weeks later. In a related study, used the same simulation in a laboratory context and found lasting gains in student understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that computer simulations can be just as useful, if not more beneficial, than paper-and-pencil activities or standard equipment. [1][2][3][4] Keller et al (2005) found in one study that there was a slight increase in student conceptual performance soon after using a computer simulation with Tutorials in Introductory Physics [5] compared to students with real equipment, but that this effect vanished upon re-examination several weeks later. In a related study, used the same simulation in a laboratory context and found lasting gains in student understanding.…”
Section: Introductionmentioning
confidence: 99%
“…First, although the effectiveness of utilizing computer simulations in conjunction with Tutorials in Introductory Physics has been previously demonstrated [16], this study investigates the impact of a computer-based environment on student learning when the computer is used rather than a teaching assistant to check student understanding at designated checkpoints within the tutorials. Second, it attempts to build upon our previously reported study which gauged the effectiveness of various levels of instructional implementation of the tutorial materials [17].…”
Section: Objectives and Methodsmentioning
confidence: 99%
“…El auge de los desarrolladores de programas se vio acompañado por una fuerte intención de evaluarlos frente a otras opciones instruccionales. Se encontraron 36 artículos en esta categoría en revistas distribuidos en AIP Conference Proceedings (2) La revisión permite, como en otras categorías, detectar un núcleo de consenso generalizado entre los autores; las simulaciones computacionales resultan más efectivas como herramienta instruccional que varias de las «tradicionales» (Chang et al, 2008;de Freitas et al, 2006;Finkelstein et al, 2005;Keller et al, 2007;Keller et al, 2006;Podolefsky et al, 2009;Podolefsky et al, 2010;Ronen y Eliahu, 2000;Smetana y Bell, 2012;Stern et al, 2008;Zacharia, 2005;Zacharia, 2007;Zacharia y Anderson, 2003). Más allá de esta concordancia en los resultados de las investigaciones, resulta imprescindible considerar los contextos en que estos se obtuvieron.…”
Section: Impactounclassified